Campylobacter jejuni Demonstrates Conserved Proteomic and Transcriptomic Responses When Co-cultured With Human INT 407 and Caco-2 Epithelial Cells - Negretti, Nicholas M.; Clair, Geremy; Talukdar, Prabhat K.; Gourley, Christopher R.; Huynh, Steven; Adkins, Joshua N.; Parker, Craig T.; Corneau, Colby M.; Konkel, Michael E. (Frontiers in Microbiology, 2019)
Major foodborne bacterial pathogens, such as Campylobacter jejuni, have devised complex strategies to establish and foster intestinal infections. For more than two decades, researchers have used immortalized cell lines derived from human intestinal tissue to dissect C. jejuni-host cell interactions. Known from these studies is that C. jejuni virulence is multifactorial, requiring a coordinated response to produce virulence factors that facilitate host cell interactions. This study was initiated to identify C. jejuni proteins that contribute to adaptation to the host cell environment and cellular invasion. We demonstrated that C. jejuni responds to INT 407 and Caco-2 cells in a similar fashion at the cellular and molecular levels. Active protein synthesis was found to be required for C. jejuni to maximally invade these host cells. Proteomic and transcriptomic approaches were then used to define the protein and gene expression profiles of C. jejuni co-cultured with cells. By focusing on those genes showing increased expression by C. jejuni when co-cultured with epithelial cells, we discovered that C. jejuni quickly adapts to co-culture with epithelial cells by synthesizing gene products that enable it to acquire specific amino acids for growth, scavenge for inorganic molecules including iron, resist reactive oxygen/nitrogen species, and promote host cell interactions. Based on these findings, we selected a subset of the genes involved in chemotaxis and the regulation of flagellar assembly and generated C. jejuni deletion mutants for phenotypic analysis. Binding and internalization assays revealed significant differences in the interaction of C. jejuni chemotaxis and flagellar regulatory mutants. The identification of genes involved in C. jejuni adaptation to culture with host cells provides new insights into the infection process.